Optimizing the Prevention of SARS-CoV-2 Transmission Through the Covid-19 Response Mosque - Andika Setiawan (AbdimasMu UMTAS, 2022)
This service aims to participate in the success of the efforts made by the management of the Al-Muttaqin prayer room in implementing health protocols according to government regulations regarding guidelines for organizing activities in houses of worship. It is also to educate the public or congregation about the meaning of Covid-19 and health protocols. This is because some people doubt that the Covid-19 virus can spread to farming communities. Because, for some of them, farmers only work in the fields. The methods used in the implementation of this service are: procurement of cleaning equipment, making liquid soap, spraying disinfectants, cleaning the prayer room, pasting posters, and distributing soap from house to house as well as an invitation to obey health protocols. The result achieved: the community or congregation became aware of the health protocol, which they then realized in the form of keeping the distance between congregations and bringing personal prayer mats from home. The prayer room management is also assisted by the procurement of cleaning equipment and additional personnel in the success of government regulations in the prayer room environment so that the implementation of health protocols is realized.